Early genetic events in the colorectal carcinogenic pathway of familial adenomatous polyposis and sporadic polyp: germline and somatic alterations in carcinogenesis - Tanabe, Hiroki; Mizukami, Yusuke; Ono, Yusuke; Takei, Hidehiro; Tamamura, Nobue; Kobayashi, Yu; Takahashi, Keitaro; Ando, Katsuyoshi; Ueno, Nobuhiro; Kashima, Shin; Tanino, Mishie; Moriichi, Kentaro; et al. (Frontiers in Genetics, 2025)
PurposeGenetic mutations in the tumor suppressor gene APC and the oncogene KRAS are an initial event in the colorectal adenoma-carcinoma sequence. Multistep carcinogenesis has been discovered through the study of familial adenomatous polyposis (FAP), an inherited disease with a germline APC variant. We aimed to determine the premalignant mutational genotypes that progress to colorectal neoplasia using target sequencing to compare the characteristics of FAP patients with sporadic cases.Experimental designA total of 197 samples from 20 FAP and 13 sporadic cases were analyzed using next-generation sequencing (NGS) with a cancer panel. The analysis of APC germline variants identified FAP patients with a germline variant, those with whole APC deletion, and those with no alterations. The association between pathogenic germline variants and somatic mutations was assessed.ResultsColorectal tumors of FAP and non-polyposis patients showed a similar frequency of mutations (APC, 76% and 75%; KRAS, 32% and 25%). Somatic APC mutations in FAP patients was observed in the mutation cluster region (63.3%). In FAP, many colorectal tumors (57.5%) harbored two APC hits, whereas in sporadic cases, one or two hits were more common (44.4% and 22.2%, respectively). Of the 99 tumors in FAP patients with APC germline variants as the first hit, 74 tumors (74.7%) acquired somatic mutations as the second hit, and 9 tumors (9.9%) further gained a third hit, indicating a ‘three-hit’ alteration.ConclusionAn identical cancer pathway may be associated with multistep carcinogenesis, accompanied by APC mutations in mutation hotspots. A combined analysis of germline and somatic alterations revealed ‘three-hit’ alterations in the APC gene among the FAP patients, suggesting that the heterogeneity of colorectal carcinogenesis contribute to these genetic changes.